Bacillus coagulans R11 maintained intestinal villus health and decreased intestinal injury in lead-exposed mice by regulating the intestinal microbiota and influenced the function of faecal microRNAs. (December 2019) - Xing, Si-Cheng; Huang, Chun-Bo; Mi, Jian-Dui; Wu, Yin-Bao; Liao, Xin-Di
Abstract: Lead contamination is an environmental problem, especially in developing countries; due to the nondegradable characteristics of lead, it is easily deposited in human and animal bodies by the food chain. Probiotics are regarded as a good tool to remove lead ions in the intestine and maintain gut health conditions, but previous studies failed to elucidate the relationship among probiotics, the host and the gut microbiota. In the present study, B. coagulans R11 was employed as the "lead removal tool" in lead-exposed mouse, and the effects of B. coagulans R11 on intestinal cells, the microbiota and faecal microRNAs were tested. The results indicated that B. coagulans R11 had no negative effects on mouse intestine model cells and helped keep cells in a normal proliferation ratio and reduce the reactive oxygen species and apoptosis ratios under lead exposure conditions. An in vivo mouse experiment also showed that B. coagulans R11 feeding could reduce the intestinal villi damage caused by lead through adjusting the microbiota structure and function, such as increasing the genus abundance of Akkermansia and Alistipes, decreasing the genus abundance of Alloprevotella, Lachnospiraceae, Parabacteroides and Ruminiclostridium, and keeping the protein dltD existing. Host faecal microRNAs may be influenced by lead and B. coagulans R11, which may change the microbiota structure. Thus, B. coagulans R11 has the potential to be developed and considered as the probiotic that protects the host gut against villi damage and gut microbiota structure and function disorders during lead exposure. Graphical abstract: Image 1 Highlights: B. coagulans R11 feeding could increase the genus abundance of Akkermansia and Alistipes in lead exposure mouse. B. coagulans R11 feeding decrease the genus abundance of four potential pathogens in lead exposure mouse. B. coagulans R11 could keep the protein dltD existing gut microbiota in lead exposure mouse. B. coagulans R11 and lead exposure all could influence the enrichment function of faecal microRNAs. B. coagulans R11 be considered as the probiotic for intestinal villi protection in lead exposure.